The morphology of corneal endothelium with the wear of hydrogel color contact lenses prescribed by unlicensed vendors / Siti Afifah Md Nor - Md Nor, Siti Afifah (Faculty of Health Sciences, 2015)
Purpose: To compare the morphology of corneal endothelium following wear of hydrogel cosmetic color contact lenses (CCL) prescribed by unlicensed vendors and authorized eye clinician. Materials and methods: Eleven research subjects who wear CCL acquired from unlicensed vendors and another eleven regular patients of Contact Lens Clinic, UiTM Puncak Alam were invited to participate in this study. All subjects were female Malays with the age range of 21 to 25 years old. The participants were assessed with preliminary routine procedures prior to endothelial photography using Tomey EM-3000 non-contact specular microscope without wearing contact lenses. The output endothelial morphological parameters were endothelial cell density (ECD), coefficient of variation (CV) and percentage of cell hexagonality. Independent-samples t-test and Mann-Whitney U test were used to verify the mean difference of the endothelial morphological parameters. Pearson’s product-moment correlation was used to determine the association of endothelial morphological changes with the duration of consuming CCL.